To buy or not to buy? Consumers’ attitudes and purchase behavior for organic food in Malaysia - Tai, Lit Cheng; Yeong, Wai Mun; Malathi Nair Narayana Nair,; Sia, Bee Chuan (Penerbit Universiti Kebangsaan Malaysia, 2020)
Organic products demand is increasing due to the awareness of the health benefits and nutritional values attached to these produces. However, in Malaysia, the organic industry is relatively small with more than 60% of the organic products being imported from overseas. Given the importance of this niche sector to the agriculture sector, marketers should understand how the consumers make decisions towards organic products. This study investigated the Malaysian organic purchasers on what affects them in their buying intention. The study uses a non-probability volunteer sampling method of 455 respondents using Structural Equation Modeling- Analysis of Moment Structures (SEM-AMOS). Results showed that health consciousness and animal welfare affects purchasing behavior directly and positively. Health consciousness, taste and food safety indirectly affect purchasing behavior while animal welfare does not have the indirect effect. This study seeks to assist organic product marketer in the development of effective marketing strategies for further increase of organic product consumption.